We have the function
![g(x)=\sqrt[3]{x+1}](https://img.qammunity.org/2023/formulas/mathematics/college/byjp82ejhpvmw557xyrpytrx6iipbvd0oo.png)
and we would like to find the inverse of it.
To do this, first we change the name of the function to y (this way is more easy to manipulate the expression), then
![y=\sqrt[3]{x+1}](https://img.qammunity.org/2023/formulas/mathematics/college/pxjzkv62rey1w546ek18s7dly7v8obsxnw.png)
Now we need to solve this equation for x, let's do this.
![\begin{gathered} y=\sqrt[3]{x+1} \\ y^3=(\sqrt[3]{x+1})^3 \\ y^3=x+1 \\ x=y^3-1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/8ibsh8n5ffpg7uke2gxe9esrmapwri54zw.png)
Once we do this the x is the inverse function. Now we relabeled the variables, x would be g^(-1) and y will be x.
Therefore
![g^(-1)(x)=x^3-1](https://img.qammunity.org/2023/formulas/mathematics/college/656hea4htwe8nxdpbquhzy8o4s8wek1hsy.png)
To make sure we are right let's do the composition between the original function and its inverse (we know that the result should be the identity function).
![\begin{gathered} (g\circ g^(-1))(x)=g(g^(-1)(x)) \\ =g(x^3-1) \\ =\sqrt[3]{x^3-1+1} \\ =\sqrt[3]{x^3} \\ =x \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/nhcu95ewso5w27ed74yp22jbwi64hhibxv.png)
since this holds, our solution is correct.